Blockholder Heterogeneity, Multiple Blocks, and the Dance between Blockholders - J Hadlock, Charles; Schwartz-Ziv, Miriam (Review of Financial Studies, 2019)
We study blockholder presence in a large panel and document substantial heterogeneity in holding periods, position sizes, and positions taken across blockholder types. Nonfinancial blocks are more likely to be observed in smaller, riskier, younger, and less-liquid firms. These patterns are either not evident or reversed for financial blocks. For all but small financial blocks, we detect significant negative interdependence in blockholder investment decisions, with the presence of one blockholder crowding out others, a behavior that appears causal. Small financial blocks often coexist in the same firm, an outcome that appears to reflect correlated investment styles. Received April 30, 2018; editorial decision November 23, 2018 by Editor David Denis.